2014
DOI: 10.1051/fruits/2014011
|View full text |Cite
|
Sign up to set email alerts
|

Annual population dynamics of mango fruit flies (Diptera: Tephritidae) in West Africa: socio-economic aspects, host phenology and implications for management

Abstract: -Introduction. Losses in West African commercial mango orchards due to fruit fly infestations have exceeded 50% by the middle of the crop season since 2005, resulting in considerable income loss for the growers. Materials and methods. In 2009, weekly monitoring of adult fruit fly species of economic significance was carried out in eight West African countries at 12 sites across five agroecological zones: (i) Humid Forest, (ii) Guinean savanna, (iii) Southern Sudan, (iv) Northern Sudan, and (v) Sahelian. Trappi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 33 publications
5
16
0
Order By: Relevance
“…Five main crop phenological stages were differentiated from this study which is consistent with the phenology stages observed by Vayssières, et al [55]. These stages, namely F/FS, FRD, M/H, FLU and D occur yearly in the mango growing areas studied.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Five main crop phenological stages were differentiated from this study which is consistent with the phenology stages observed by Vayssières, et al [55]. These stages, namely F/FS, FRD, M/H, FLU and D occur yearly in the mango growing areas studied.…”
Section: Discussionsupporting
confidence: 90%
“…This includes the dates physiological changes e.g., flowering, fruitset and leaf flush were first observed and farm management activities such as flower induction dates and harvesting were undertaken. Additionally, published literature relating to mango phenology cycles in Ghana and West Africa were reviewed [55,56]. The information indicated the growth stages and timings (Figure 2) where the collection of monthly satellite data was most required.…”
Section: Study Areamentioning
confidence: 99%
“…C. cosyra is the second most important species to which special attention must be paid in Togo and in West Africa (Ouédraogo et al 2011;Zida et al 2020). This species was considered as adapted to Sahelian and Sudanese zones and absent from agro-ecological zones of the humid forests of West Africa (Vayssières et al 2014). However, it was found in all ecological zones of the study area in Togo including zone IV dominated by dense semi-deciduous forests.…”
Section: Discussionmentioning
confidence: 99%
“…Of insect pests attacking fruits and vegetables fruit flies (Diptera: Tephritidae) ranked as being one of the most important economically. The losses attributed to fruit flies in sub-Saharan Africa have been increasing in recent years because, in addition to the indigenous species like Ceratitis cosyra (Walker) (Diptera: Tephritidae) which attack fruits and reduce their nutritional and trade values, a new species, Bactrocera dorsalis (Hendel) (Diptera: Tephritidae) originated from Southeast Asia was first detected in Kenya in 2003, was introduced from Southeast Asia (Pouillès-Duplaix 2008;Vayssières et al 2014). In a few years, this species has spread throughout West Africa (Drew et al 2005), as an invasive species.…”
Section: Introductionmentioning
confidence: 99%
“…For a century, Tephritidae has been one of the most studied pests (Passion Entomology, 2014). They cause considerable economic losses for farmers (Vayssières et al, 2014). The study has been carried out on the unspecified infestation rate of mango varieties in Benin (Vayssières et al, 2010) and Togo (Gomina, 2015).…”
Section: Introductionmentioning
confidence: 99%